Memory Foam Pillow as an Intervention in Obstructive Sleep Apnea Syndrome: A Preliminary Randomized Study - Stavrou, Vasileios T.; Koutedakis, Yiannis; Astara, Kyriaki; Vavougios, George D.; Papayianni, Eirini; Stavrou, Ilias T.; Bardaka, Fotini; Pastaka, Chaido; Gourgoulianis, Konstantinos I. (Frontiers in Medicine, 2022)
Specific pillow use is a seldom studied or controlled factor in the setting of sleep disordered breathing. The aim of this study was to investigate the effect of different pillows [own pillow (OP), memory foam pillow (MFP), generic laboratory pillow (LP)] on polysomnography (PSG)-derived parameters in patients with Obstructive Sleep Apnea Syndrome (OSAS). Thirty-two consecutive patients with OSAS were randomly allocated into two groups with randomized pillow usage [Group A: 3 h with LP and 3 h with OP (Age: 53.8 ± 12.5 years, BMI: 32.1 ± 4.6 kg/m2); Group B: 3 h with LP and 3 h with MFP (Age: 52.0 ± 6.3 years, BMI: 30.6 ± 2.2 kg/m2)]. Statistically significant differences between pillow types were detected in desaturation index and heart rate. In Group B (with MFP), a statistically significant decrease of 47.0 ± 15.9% was observed in snoring events (p < 0.05) and 10.6 ± 6.7% in their duration (p < 0.05) compared to LP. On the other hand, group A with OP recorded a decrease of 29.1 ± 32.1% in snoring events and 32.5 ± 33.1% in duration, but these values were not statistically significant (p > 0.05) compared to LP. These findings indicate that pillow type and usage, often uncontrolled in OSAS studies (contribution to the field), may impact several PSG parameters and are related to a snoring subtype of the syndrome. Secondly, they indicate that a focus on the treatment of the snoring OSAS subtype warrants further dedicated investigation.